A Randomized Clinical Trial Examining the Effects of Instructions for Electronic Cigarette Use on Smoking-Related Behaviors and Biomarkers of Exposure. Issue 9 (12th December 2019) - Hatsukami, Dorothy K; Meier, Ellen; Lindgren, Bruce R; Anderson, Amanda; Reisinger, Sarah A; Norton, Kaila J; Strayer, Lori; Jensen, Joni A; Dick, Laura; Murphy, Sharon E; Carmella, Steven G; Tang, Mei-Kuen; et al.
Abstract: Introduction: Electronic cigarettes (e-cigarettes) have the potential to significantly reduce exposure to harmful constituents associated with cigarette smoking when smokers completely substitute cigarettes with e-cigarettes. This study examined patterns of e-cigarette and cigarette use, and extent of toxicant exposure, if smokers were instructed and incentivized to completely switch to e-cigarettes compared to instructions to use the product ad libitum . Aims and Methods: US adult daily smokers ( n = 264; 49.2% female; M age = 47.0), uninterested in quitting smoking immediately, were recruited from Minneapolis, MN, Columbus, OH, and Buffalo, NY. Participants were randomized to 8 weeks of instructions for (1) ad libitum use of e-cigarettes (AD-E), (2) complete substitution of cigarettes with e-cigarettes (CS-E), (3) complete substitution of cigarettes with nicotine gum or lozenge (CS-NRT), or (4) continue smoking of usual brand cigarettes (UB). Participants were incentivized for protocol compliance, including complete switching in the CS-E and CS-NRT groups. Outcome variables were cigarette smoking rate and tobacco-related biomarkers of exposure. Results: Smokers in the CS-E and CS-NRT groups showed lower rates of smoking and lower exposure to carbon monoxide, tobacco carcinogens, and other toxicants than smokers in the AD-E group. In general, no significant differences were observed between CS-E versus CS-NRT or between AD-E versus UB for most biomarkers. Significantly higher 7-day point prevalence smoke-free rates were observed for CS-E versus CS-NRT. Conclusions: Smokers instructed and incentivized to completely switch to e-cigarettes resulted in lower smoking rates and greater reductions in exposures to harmful chemicals than smokers instructed to use the product ad libitum . Implications: Smokers instructed to completely substitute e-cigarettes for cigarettes displayed significantly lower levels of smoking and biomarkers of exposure to carcinogens and toxicants, compared to smokers instructed to use e-cigarettes ad libitum and similar levels as smokers instructed to completely substitute with nicotine replacement therapies. Furthermore, a higher rate of complete switching was achieved with e-cigarettes versus nicotine replacement therapies. Approaches to maximize complete substitution with e-cigarettes are an important area for future research.